Technology and AI’s role in multicultural and digital leadership - Paiuc, Dan (Proceedings of the International Conference on Networked Learning, 2024)
This research aims to present a systematic literature review focusing on technology and artificial intelligence (AI) as new vectors for multicultural and digital leadership. With 80% of companies using at least one emerging technology for finance and operations, 58% of firms increasing their spending in AI for workforce planning, and a big data market projected to be worth 77 billion before the end of 2023, multicultural and digital leaders (ML; DL) have to adapt and acknowledge, integrate, and leverage technology into their daily business management (FinancesOnline, 2023). The conference paper intends to introduce an up-to-date systematic literature review and a bibliographic investigation performed with VOSviewer software, focusing on technology and AI as new vectors of multicultural and digital leadership. Mining into the Web of Science Core Collection database, our research creates an evident visual representation of the interconnectedness between technology, AI, ML, and DL. As the global business landscape increasingly values digital leadership, this bibliometric analysis offers valuable tools for multicultural and digital business leaders as well as academic researchers to comprehend, shape, and leverage the dynamics of these evolving domains.